2009
DOI: 10.1007/s11250-009-9382-z
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of bovine brucellosis and its risk factors in Jimma zone of Oromia Region, South-western Ethiopia

Abstract: A cross sectional sero-prevalence study was conducted on 1,595 cattle in Jimma zone, Ethiopia to investigate the status of bovine brucellosis and identify potential risk factors. Sera samples were analyzed using Rose Bengal Plate Test (RBPT) and Complement Fixation Test (CFT). The overall individual and herd level sero-prevalences were 3.1% (n = 1,595) and 15.0% (n = 227), respectively. The sero-prevalence of bovine brucellosis at individual animal level was significantly higher in non-pregnant (11.18%) than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
72
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 11 publications
23
72
5
Order By: Relevance
“…(Nielsen et al 2004). The observed brucellosis seroprevalence results agree with those of previous studies in Zimbabwe (Madsen, 1989;Mohan et al 1996) and those from smallholder farming areas in other regions (Bayemi et al 2009;Ibrahim et al 2010;Karimuribo et al 2007). However, higher brucellosis seroprevalence have been recorded in individual cattle from traditional smallholder herds in other areas (Chimana et al 2010;Faye et al 2005;Muma et al 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(Nielsen et al 2004). The observed brucellosis seroprevalence results agree with those of previous studies in Zimbabwe (Madsen, 1989;Mohan et al 1996) and those from smallholder farming areas in other regions (Bayemi et al 2009;Ibrahim et al 2010;Karimuribo et al 2007). However, higher brucellosis seroprevalence have been recorded in individual cattle from traditional smallholder herds in other areas (Chimana et al 2010;Faye et al 2005;Muma et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The fact that brucellosis was low in areas with small median herd sizes showed that the risk of transmission of Brucella spp. among cattle was low in small herds (Ibrahim et al 2010). However, the observed results for Gokwe may be contributed by a high proportion of farms that shared facilities for grazing and watering of cattle compared to the other study areas which kept their herds as self-contained units (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…Perusal of the literature indicated prevalence of brucellosis in western region (Gujarat state) was ranging from 8.98 to 44.00% (Sutariya et al 2005;Chauhan et al 2000), 17% in southern region (Isloor et al 1998), 6.3% in central region (Madhya Pradesh state) (Mehra et al 2000) and 12.9% in northern region (Punjab state) (Dhand et al 2005). In other countries, sero-prevalence of brucellosis was reported to be 3.1% in Ethiopia (Ibrahim et al 2009), 6.5% in Jordan (Al-Majali et al 2009), 8.4% in Cameroon (Bayemi et al 2009) and 32.92 to 39.45% in Turkey (Sahin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of brucellosis in the 1970s in Ethiopia, the disease has been noted as one of the important livestock diseases in the country (Asfaw, 1998;Eshetu et al, 2005;Kebede et al, 2008;Ibrahim et al, 2010). Prevalence of bovine brucellosis varies widely across Ethiopia, with reported seroprevalences ranging from 0.2% in south-western Ethiopia (Tolosa, 2004) to 38% in western Ethiopia (Rashid, 1993).…”
Section: Introductionmentioning
confidence: 99%